Past fame, present frames and future flagship? An exploration of how health is positioned in Canadian foreign policy - Ronald Labonté; Vivien Runnels; Michelle Gagnon (Administrative Sciences, 2012)
Canada has been regarded as a model global citizen with firm commitments to multilateralism. It has also played important roles in several international health treaties and conventions in recent years. There are now concerns that its interests in health as a foreign policy goal may be diminishing. This article reports on a thematic analysis of key Canadian foreign policy statements issued over the past decade, and interviews with key informants knowledgeable of, or experienced in the interstices of Canadian health and foreign policy. It finds that health is primarily and increasingly framed in relation to national security and economic interests. Little attention has been given to human rights obligations relevant to health as a foreign policy issue, and global health is not seen as a priority of the present government. Global health is nonetheless regarded as something with which Canadian foreign policy must engage, if only because of Canada's membership in many United Nations and other multilateral fora. Development of a single global health strategy or framework is seen as important to improve intersectoral cooperation on health issues, and foreign policy coherence. There remains a cautious optimism that health could become the base from which Canada reasserts its internationalist status.
Keywords: 350; global health; foreign policy; Canada; security; trade; development; human rights; global health diplomacy